Replacement options for the B2 glenoid in osteoarthritis of the shoulder: a biomechanical study - Sowa, Boris; Bochenek, Martin; Braun, Steffen; Zeifang, Felix; Kretzer, Jan Philippe; Bruckner, Thomas; Walch, Gilles; Raiss, Patric (Archives of orthopaedic and trauma surgery, 2018)
Background: Glenoid replacement in cases of severe glenoid retroversion (RV) or eccentric wear is challenging. The aim of this study was to evaluate different treatment methods under standardized conditions to assist surgeons in the decision-making process. - METHODS: Three treatment options for severe glenoid RV (15°) were compared: (1) no RV correction; (2) complete RV correction; (3) no RV correction and implantation of a posterior augmented glenoid (PAG). A highly standardized implantation protocol using artificial glenoid bones (five per group) was chosen, and a physiologic shoulder movement was applied in a biomechanical setting. Micromotions (MM) between glenoid components and bone were quantified using an optical 3D measuring system. - RESULTS: In the uncorrected retroversion group, three instances of subluxation of the prosthetic head occurred between 2000 and 4000 cycles. At 2000 cycles, significantly more MM were observed in the uncorrected RV group than in the corrected RV group (p < 0.0001) or to the augmented group (p < 0.0001). At 10|000 cycles, more MM were observed in the posterior augmented group than in the corrected RV group (p < 0.0001). - CONCLUSION: If sufficient bone stock is available, retroversion correction should be favored. Posterior augmented glenoids seem to be a suitable treatment option if complete correction of the retroversion is not possible without compromising the glenoid vault. Without correction of the retroversion, high failure rates were observed.
Gesehen am 01.04.2020